Laparoscopic Suture versus Mesh Rectopexy for the Treatment of Persistent Complete Rectal Prolapse in Children: A Comparative Randomized Study - Yehya, AbdelAziz (Minim Invasive Surg, 2020)
PURPOSE: To compare laparoscopic mesh rectopexy with laparoscopic suture rectopexy. Patients and Methods. The prospective study was conducted at Pediatric Surgery Department, Al-Azhar University Hospitals, Cairo, Egypt between Feb 2010 and Jan 2015. Seventy-eight children with persistent complete rectal prolapse were subjected to laparoscopic rectopexy. Fourteen parents refused to participate. All patients received initial conservative treatment for more than one year. The remaining 64 patients were randomized divided into two equal groups. Group A; 32 patients underwent laparoscopic mesh rectopexy and group B, 32 underwent laparoscopic suture rectopexy. The operative time, recurrence rate, post-operative constipation, and effect on fecal incontinence, were reported and evaluated for each group. RESULTS: Sixty-four cases presented with persistent complete rectal prolapse were the material of this study. They were 40 males and 24 females. Mean age at operation was 8 (5–12) years. All cases were completed laparoscopically. Mean operative time in laparoscopic suture rectopexy was shorter than laparoscopic mesh rectopexy group. No early post-operative complications were encountered. No cases of recurrence with mesh rectopexy group while in suture rectopexy group it was 4 cases (14.2%). Post-operative constipation occurred in one case (3.57%) in suture rectopexy group and occurred in one case (3.3%) in mesh rectopexy group. Fecal incontinence improved in 26/28 cases (92.8%) in suture rectopexy while in mesh rectopexy it was improved in 30/30 cases (100%) of cases. CONCLUSION: Both laparoscopic mesh and suture rectopexy are feasible and reliable methods for the treatment of complete rectal prolapse in children. However, no recurrence, low incidence of constipation and high improvement of incontinence at follow up more than 36 months with mesh rectopexy accordingly, we considered mesh rectopexy to be the procedure of choice in treatment of complete rectal prolapse.